2017
DOI: 10.18805/ijare.v0iof.7628
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and association study for grain yield in germplasm accessions of maize (zea mays L.)

Abstract: The present investigation aimed to find out the association among yield and its components and to sort out the traits that are directly or indirectly contributing towards yield in landraces of maize genotypes. The eighty eight (88) maize germplasm collections were used in present study during Kharif -2012 and Kharif -2013 in RCBD design. Pooled data and standard statistics were employed (means, ranges, GM±SE, standard error and coefficient of variation etc.) for analysis of the seventeen quantitative traits to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…By selecting for these characters that reveal positive and strong relation with grain yield, there is possibility of increasing maize grain yield therefor in the process of selection, much attention should be given to these traits which are helpful to improve yield on the basis of indirect selection. In literature similar results were recorded by (Choudhary and Chaudary, 2002;Chinnadurai and Nagarajan, 2011;Charles et al, 2013;Kumar et al, 2014;Nzuve et al, 2014;Kinfe and Tsehaye, 2015;Ajmal et al, 2016;Rahman et al, 2016;Kharel et al, 2017;Rahman et al, 2017;Shukla, 2017;Beulah et al, 2018 andBartaula et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…By selecting for these characters that reveal positive and strong relation with grain yield, there is possibility of increasing maize grain yield therefor in the process of selection, much attention should be given to these traits which are helpful to improve yield on the basis of indirect selection. In literature similar results were recorded by (Choudhary and Chaudary, 2002;Chinnadurai and Nagarajan, 2011;Charles et al, 2013;Kumar et al, 2014;Nzuve et al, 2014;Kinfe and Tsehaye, 2015;Ajmal et al, 2016;Rahman et al, 2016;Kharel et al, 2017;Rahman et al, 2017;Shukla, 2017;Beulah et al, 2018 andBartaula et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Positive association of grain yield per plant with days to maturity, plant height, ear height, ear length, ear girth, number of kernel rows per plant, number of kernels per row, 100-kernel weight and shelling percentage in also reported by Kumar et al, (2014). Positive and highly significant correlation of grain yield with ear height, days to 50% male flower initiation, days to 50% female flower initiation, days to maturity, 1000 grain weight, ear weight at genotypic and phenotypic level also reported by Shukla, (2017). Positive relationship of ear girth, kernels per row and ear length with grain yield per plant has also reported by Sumalini and Manjulatha, (2012).…”
Section: Resultsmentioning
confidence: 61%
“…In addition, the genetic variability from parents to offspring were also found in the plants such as bringjal (G. Samlind sujin et al, 2017), rice (Pradhan et al, 2017), maize (Niharika 2017;Yan et al 2017) and speciality corn (Divya et al 2017) and the performance of some agronomic traits in hybrids were generally found to be different from their parents in crops (Qu et al, 2012;Qi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%